The Influence of Employee Maturity, Work Ability, Work Discipline and Loyalty on Employee Performance at the Madya Dua Tax Service Office South Jakarta II - Tambunan, Cherish Rosari; Panjaitan, Hesty Triana; Putra, Rici Santridin; Mayasari, Rika; Pane, Sri Gustina; Rahayu, Sri (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the effect of employee maturity, work ability, work discipline and loyalty partially and simultaneously on the performance of employees work in the Kantor Pelayanan Pajak Madya Dua Jakarta Selatan II with a population of 118 people, and a study sample. of 54 people. The data analysis technique used is multiple regression analysis. Based on the analysis results obtained employee maturity has a not effect on the performance of employees work of the Kantor Pelayanan Pajak Madya Dua Jakarta Selatan II, this is supported by the results of t count analysis < t-table (0,379 < 2,010) at n = 54 at 95% significance level